NaCl-induced hot corrosion behaviors of NiSiAlY coatings - Yu, Miao; Zhou, Dapeng; Zhu, Bing; Cui, Tiancheng; Lu, Yang; Wang, Yongxin (Frontiers in Materials, 2023)
In the marine environments, NiCrAlY coatings with high content of Cr would suffer much severer corrosion due to the effect of NaCl. Thus, NiSiAlY coatings with different Si content were proposed and deposited on Ni-based superalloys by multi-arc ion plating. The as-deposited coating was mainly composed of γ’-Ni3Al phase with a small amount of β-NiAl phase. NaCl-induced hot corrosion tests were performed on the coatings at 500°C, 600°C, and 700°C, respectively. Compared with Ni-based alloy substrates, the NiSiAlY coatings exhibited a good corrosion resistance to NaCl at elevated temperatures. However, with an excessive amount of Si, the NiSiAlY coating showed a degradation in the hot corrosion resistance. In this work, the corrosion mechanisms of the tested coatings were discussed. Moreover, the role of Si was also investigated.